Pendidikan Inklusi dalam Al-Qur’an Berdasarkan Surat ‘Abasa Ayat 1-11 - Fusvita Dewi (IAIN Bengkulu, 2023)
In the world of education, the level of awareness in socializing has decreased a lot, which has made the Indonesian nation more anarchic and differentiates other individuals. Evidenced by the emergence of various kinds of crimes that occur due to negligence in education that does not respond to any behavior that is not by goodness. The solution to addressing this is inclusive education which must be instilled in education as contained in the letter Abasa verses 1-11. The method for collecting data is using library research, namely by taking sources from books, journals, and previous research. In this article, we find several opinions of mufassir who expressed their opinion about inclusive education contained in the letter 'Abasa verses 1-11, for example, Buya Hamka in the interpretation of al-Azhar, Quraish Shihab in the interpretation of al-Misbah, the interpretation of Ibn Katsir, the interpretation of al-Jalalain and Wahbah as-Zuhaili in al-Tafsir al-Munir fil Aqidati was al-Shariati was al-Minhaji. Inclusive education is one of the ways to overcome differences in supporting education as in the letter 'Abasa verses 1-11 which teaches us not to discriminate against other people in society, nation, and state.